Gender equality in sickness absence tolerance: Attitudes and norms of sickness absence are not different for men and women - Løset, Gøril Kvamme (PLoS One, 2018)
Previous research offers limited understanding as to why sickness absence is higher among women than among men, but attitudes and norms have been suggested as plausible explanations of this gender gap. The purpose of the present study is to examine whether the gender gap in sickness absence reflects gender differences in sickness absence attitudes or gendered norms of sickness absence in society. The analyses are based on data from a factorial survey experiment covering 1,800 male and female employed respondents in Norway in 2016. Each participant was asked to evaluate whether sick leave would be reasonable in six unique, hypothetical sickness absence scenarios (i.e. vignettes) in which occupation, gender and reason for sick leave varied. Sick leave judgments were regressed on respondent gender and vignette gender using binary logistic regressions across three cut points. Overall, we did not find a substantial gender difference in either attitudes towards sickness absence or sickness absence norms. However, further analyses indicated more tolerant social norms of sickness absence for employees in gender-dominated occupations than for employees in gender-integrated occupations. This pattern could be a result of the type of work attributed to these occupations rather than their gender composition. Contrary to popular belief, we conclude that widely held attitudes and norms of sickness absence are unlikely to be drivers of the gender gap in sickness absence. The results can be useful for policies and interventions aimed at safeguarding gender equality in the labour market.